EFL Students’ Ability to Translate Conversational Implicatures from the American Sitcom Modern Family into Standard Indonesian - Angellia Puspita Anwar; Risnawati Risnawati; Pebri Prandika Putra (The Future of Education Journal, 2026)
This study aims to identify the most dominant translation strategies and evaluate the success rate of students in maintaining pragmatic meanings when translating implicit conversations from the American sitcom Modern Family into Indonesian, using the framework of Peter Newmark (1988) and Grice HP (1989) this study examines how successful EFL students' ability to understand the implicit meanings contained in conversations. This study uses a quantitative descriptive method. The results showed that students used five translation strategies, namely Literal Translation (35%), Word-for-Word Translation (10%), Faithful Translation (7%) and Idiomatic Translation (6%). The Literal Translation strategy is the most dominant strategy used by EFL students, indicating a tendency to prioritize linguistic forms over pragmatic meanings. Meanwhile, the overall success rate in understanding the meaning of pragmatism was at the level of "Successful" (63%) and "Fairly successful" (38%) with no students achieving "Very successful" and "Less successful". Based on the success of understanding pragmatic meaning based on Maxim Grice, students were most successful in understanding the maxim of quality (65%), maxim of quantity (61%), maxim of relevance (57%) and maxim of manner (56%), this shows that EFL students are able to understand implications that contain sarcasm, hyperbole, and incomplete information. It can be concluded that the choice of strategies used by students affects the quality of translation of implicit meanings in implicit conversations.